2011
DOI: 10.3340/jkns.2011.50.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression in the Rat Hippocampus after Focal Cerebral Ischemia

Abstract: Objective : The rat middle cerebral artery thread-occlusion model has been widely used to investigate the pathophysiological mechanisms of stroke and to develop therapeutic treatment. This study was conducted to analyze energy metabolism, apoptotic signal pathways, and genetic changes in the hippocampus of the ischemic rat brain. Methods : Focal transient cerebral ischemia was induced by obstructing the middle cerebral artery for two hours. After 24 hours, the induction of ischemia was confirmed by the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In our study, expression of TNF receptors upregulated in the hippocampus after both LPS and MCAO included Tnfrsf1a, Tnfrsf12a, and Tnfrsf26. The increase in Tnfrsf1a expression in the hippocampus of rats 24 h after ischemia was reported previously [11], and our data support this result. GO BP terms "inflammatory response", "response to lipopolysaccharide", and "regulation of cell proliferation" were mainly enriched with LPS-responding genes, including Tnfrsf1a and Tnfrsf26, and the numbers of these LPS-responding genes were 10 (Ccl2, Cd14, Hck, Tnfrsf1a, Anxa1, Casp4, Spp1, S1pr3, Thbs1, Tnfrsf26) from 17, 11 (Ccl2, Cd14, Fos, Tnfrsf1a, Csf2rb, Lbp, Ptges, Serpine1, Socs3, Trib1, Tnfrsf26) from 15, and 9 (Fgr, Hck, S100a11, Tnfrsf1a, Anxa1, B4galt1, Irf1, Serpine1, Tnfrsf26) from 11, accordingly.…”
Section: Inflammatory Responsesupporting
confidence: 93%
“…In our study, expression of TNF receptors upregulated in the hippocampus after both LPS and MCAO included Tnfrsf1a, Tnfrsf12a, and Tnfrsf26. The increase in Tnfrsf1a expression in the hippocampus of rats 24 h after ischemia was reported previously [11], and our data support this result. GO BP terms "inflammatory response", "response to lipopolysaccharide", and "regulation of cell proliferation" were mainly enriched with LPS-responding genes, including Tnfrsf1a and Tnfrsf26, and the numbers of these LPS-responding genes were 10 (Ccl2, Cd14, Hck, Tnfrsf1a, Anxa1, Casp4, Spp1, S1pr3, Thbs1, Tnfrsf26) from 17, 11 (Ccl2, Cd14, Fos, Tnfrsf1a, Csf2rb, Lbp, Ptges, Serpine1, Socs3, Trib1, Tnfrsf26) from 15, and 9 (Fgr, Hck, S100a11, Tnfrsf1a, Anxa1, B4galt1, Irf1, Serpine1, Tnfrsf26) from 11, accordingly.…”
Section: Inflammatory Responsesupporting
confidence: 93%
“…Several studies confirmed apoptotic cell death in hippocampus after 24 h of ischemia in different rat strain (15, 41, 42). Our results are parallel to previous published reports, found apoptotic cell death in hippocampus after 24 h of ischemia (41, 43). Moreover, these authors found no changes in Caspase and Bcl-2 expression in hippocampus using I/R model.…”
Section: Discussionmentioning
confidence: 84%
“…Another study found that ATP5G2 was upregulated in an ischaemic rat brain model. The authors described upregulated ATP5G2 gene expression 24 h after artery occlusion [44], suggesting that ATP5G2 gene expression is an early hypoxia/ischaemia response gene. The role of the expression of genes like ATP5G2 in gliomas needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that ATP5G2 was upregulated in an ischaemic rat brain model. The authors described upregulated ATP5G2 gene expression 24 h after artery occlusion [44],…”
Section: Discussionmentioning
confidence: 99%